The Mediating Effects of Corporate Governance on the Relationship Between Opinion Audit and Audit Delay: A Study on Mining Companies Listed on IDX Period 2017 – 2018 - Sisobadodo Zendrato; Francis Hutabarat (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
This study was chosen because it has a certain urgency and purpose, namely to find out that the mediating effect of corporate governance on the relationship between audit opinion has an influence on audit delay. The results of research tests that have been carried out show descriptive statistical results in this study related to the characteristics of the variables in the study. Regarding profitability, it was found that the Audit Delay has an average of 65.5 days within the 90 days period of the publication of the company's audit report on the Indonesia Stock Exchange. Another thing that was found was related to the independent variable, namely the average value of the Audit Opinion was 0.22 indicating that most of the audit reports had a Qualified statement. Regarding corporate governance, the proxy balance between the Independent Commissioners found that the average size of the PDKI is 35.89% which is above the 30% standard. Thus the results of descriptive statistics show that on average the implementation of audit delay, audit opinion and corporate governance is in accordance with applicable standards. With the results of the tests that have been conducted, it is found that there is no effect of audit opinion on audit delay, whereas with the mediation of governance or also known as corporate governance on audit delay, there is a significant effect. Thus, the existence of Corporate Governance fully mediates the effect of Audit Opinion on Audit Delay.